Global youth tobacco survey 2022 for developing tobacco control policies in Thailand - Sittibusaya, Chayanan; Benjakul, Sarunya; Noonak, Onnicha; Tontiram, Ruthchaya; Nalaem, Chaiwat; Sakulsawat, Tanyaporn; Palaphon, Thaweekhun (Disease Control Journal, 2025)
This study aimed to monitor the situation regarding tobacco product consumption behaviors among Thai youths aged 13 to 15 years. The target population consisted of 6,752 students aged 13 to 15 years, enrolled in schools under the Office of the Basic Education Commission and the Office of the Private Education Commission. The study found that 12.5% of the students regularly used all types of tobacco products (such as cigarette, cigars, and smokeless tobacco); 8.1% use cigarettes. It was found that currently, 17.6% of students smoked e-cigarettes regularly. Exposure to second-hand smoke at home was reported by 26.0% and at school by 45.6%. In the past 30 days, 31.7% of students noticed advertisements or promotions for cigarette packs or other tobacco products on the internet, 48.0% noticed e-cigarette advertisements on social media, and 25.6% reported having seen tobacco product promotions at points of sale. Additionally, 11.1% of students reported receipt of free cigarettes or tobacco products from cigarette distributors. The survey results reflect a significant increase in e-cigarette use among students, rising 5.3 times from 3.3% in 2015 to 17.6% in 2022. Marketing strategies of the tobacco industry, particularly online advertising, have increasingly targeted children and adolescents. Moreover, lifestyle values and attitudes of youth toward smoking have shifted. Thailand urgently needs to implement preventive and control measures to curb the spread of e-cigarettes in the country. To address this issue seriously and elevate it to a national agenda, a set of preventive and control measures for e-cigarette use in Thailand has been developed to curb the spread of e-cigarette use among children and adolescents.